A new chemotherapeutic approach using doxorubicin simultaneously with geopropolis favoring monocyte functions - Oliveira, Lucas Pires Garcia [UNESP]; Conte, Fernanda Lopes [UNESP]; de Oliveira Cardoso, Eliza [UNESP]; Conti, Bruno José [UNESP]; Santiago, Karina Basso [UNESP]; de Assis Golim, Marjorie [UNESP]; da Silva Feltran, Geórgia [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Sforcin, José Maurício [UNESP] (Elsevier, 2019)
Aims: Chemotherapy has been widely used to treat cancer although it may affect non-target cells involved in the immune response. This work aimed at elucidating whether the chemotherapeutic agent doxorubicin in combination with geopropolis produced by Melipona fasciculata Smith could affect nontumor immune cells, evaluating their immunomodulatory effects on human monocytes. Main methods: Cell viability, expression of cell markers (HLA-DR, TLR-2, TLR-4, C80 and CD40), cytokine production (TNF-α IL-1β IL-6 and IL-10), intracellular pathways (NF-κB and autophagy), the microbicidal activity of monocytes and hydrogen peroxide (H 2 O 2 ) production were analyzed. Key findings: Data showed that doxorubicin + geopropolis diminished IL-6 secretion, stimulated TNF-α and IL-10 production, TLR-4 and CD80 expression, NF-κB and autophagy pathway, as well as the bactericidal activity. Significance: Our findings revealed a new chemotherapeutic approach using doxorubicin simultaneously with geopropolis without affecting human monocytes viability and exerting immunomodulatory effects, favoring cell functions. While doxorubicin altered some immunological parameters, the addition of geopropolis compensated some changes.
Keywords: Chemotherapy; Geopropolis; Immunomodulation; Monocytes